2006
DOI: 10.4067/s0718-19572006000200001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and shell utilization in three sympatric hermit crabs at non-consolidated sublittoral of estuarine-bay complex in São Vicente, São Paulo, Brazil

Abstract: Spatial distribution and shell utilization in three sympatric hermit crabs at non-consolidated sublittoral of estuarine-bay complex in São Vicente, São Paulo, Brazil Abstract.-The objective of the present study was to characterize the spatial distribution and shell utilization of three hermit crab species in the estuarine-bay complex of São Vicente, São Paulo State, Brazil. Monthly samples were done throughout two years, in the non-consolidated sub-littoral at the estuarine-bay complex. The environmental facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is known that the Amazon River can act as a physical barrier to many marine species, especially against larval phases in which survival is critical. Low salinity in the river drainage could be a limiting abiotic factor for some larval and adult species of the family Mithracidae, just as salinity is limiting factor for some species of hermit crabs (Sant'Anna, Zangrande, Reigada, & Severino‐Rodrigues, ). This could explain the observed variability between the specimens of Brazil (Brazilian Province) and Venezuela and/or Belize (Caribbean Province).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the Amazon River can act as a physical barrier to many marine species, especially against larval phases in which survival is critical. Low salinity in the river drainage could be a limiting abiotic factor for some larval and adult species of the family Mithracidae, just as salinity is limiting factor for some species of hermit crabs (Sant'Anna, Zangrande, Reigada, & Severino‐Rodrigues, ). This could explain the observed variability between the specimens of Brazil (Brazilian Province) and Venezuela and/or Belize (Caribbean Province).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies previously carried out in the Brazilian subtropical region, Negreiros- Fransozo et al (1991) found that 100% of the hermit crabs C. symmetricus (vittatus) occupied shells of the genus Thaisella (Thais). In other studies, the gastropod shell species most frequently used by C. symmetricus in a natural environment was Stramonita haemastoma (Linnaeus, 1767) (Reigada and Santos 1997;Sant'Anna et al 2006aMantelatto et al 2010;Sampaio and Masunari 2010). The preference for S. haemastoma was reported in laboratory experiments by Turra and Leite (2002).…”
Section: Discussionmentioning
confidence: 97%
“…Shell occupancy does not occur randomly, but is rather influenced by several factors, such as shell availability in nature, weight, size, shape and/or internal shell volume, suitability of shell size and shape, or even intra-and interspecific competition among hermit crabs (Martinelli and Mantelatto 1999;Mantelatto and Garcia 2000;Garcia and Mantelatto 2001;Meireles et al 2003;Dominciano and Mantelatto 2004;Mantelatto and Meireles 2004;Meireles and Mantelatto 2005;Biagi et al 2006b;Sant'Anna et al 2006a;Fransozo et al 2008). The presence of epibionts on shells is also a factor that may provide camouflage in combination with the substrate and influence the shell selection by hermit crabs (Martinelli and Mantelatto 1998; Ayres-Peres and Mantelatto 2010; Ribeiro et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Located along the northern coastline of the state of São Paulo, the Ubatuba region is an important area for crustacean research . The spatial and temporal distribution of a species results from aspects of the animal's biology such as the feeding mode, behavior and local characteristics ( NegreirosFransozo et al 1997;Sant'Anna et al 2006).…”
Section: Introductionmentioning
confidence: 99%